Percentage of Gutta-Percha-, Sealer-, and Void-Filled Areas in Oval-Shaped Root Canals Obturated with Different Filling Techniques: A Confocal Laser Scanning Microscopy Study - Hirai, Vinicio Hidemitsu Goto; Machado, Ricardo; Budziak, Maria Carolina Lucato; Piasecki, Lucila; Kowalczuck, Alexandre; Neto, Ulisses Xavier da Silva (European Journal of Dentistry, 2020)
Objective This study compared different obturation techniques, analyzing percentage of areas filled with gutta-percha, sealer, and voids (PGFA, PSFA, and PVFA, respectively) in oval-shaped root canals.Materials and Methods A total of 60 extracted human mandibular central incisors were decoronated, instrumented, and irrigated using the same protocol. After drying, the root canal was filled with AH Plus labeled with 0.1% rhodamine B dye using a Lentulo spiral. The filling procedure was performed by dividing the teeth into four groups according to the respective technique: G1, cold lateral condensation; G2, continuous wave of condensation; G3, modified cold lateral condensation using an F3 master cone; and G4, modified continuous wave of condensation using an ISO (International Organization for Standardization) sized 30 gutta-percha cone. Then, slices measuring 1.5 mm in thickness were obtained 3 and 6 mm from the apex and evaluated by confocal laser scanning microscopy to determine PGFA, PSFA, and PVFA.Statistical Analysis The data were analyzed statistically with analysis of variance and Games-Howell’s tests (p = 0.05).Results The groups showed no significant differences in the apical third (3 mm from the apex). In the middle third (6 mm from the apex), G3 and G1 showed higher PGFA and PVFA, respectively. G3 showed lower PSFA than G2 and G4. Both cold techniques (G1 and G3) promoted lower PSFA than both warm techniques (G2 and G4).Conclusions Notwithstanding the limitations of this in vitro study, PGFA, PSFA, and PVFA ranged significantly only in the middle third, as observed by the different filling techniques. Higher PGFA and PVFA values were obtained for G3 and G1, respectively. Both cold techniques promoted lower PSFA than both warm techniques.
Keywords: oval-shaped canals; gutta-percha-filled area; sealer; voids; filling techniques